Strategy In Overcoming Barrier In Listening English - Fadila, Nazifah Ayu (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The application of listening techniques with music must be very effective every day so that the results can be seen, and must be done with an introduction to grammar and other grammar in English. and this technique must be carefully considered, such as students' language skills and strategies that can be used when learning and teaching according to the explanation above, the author is very interested in conducting research on the listening learning program at the Islamic University of North Sumatra, on students in the second semester of Stambuk 23. to find out the learning program that is implemented in the classroom. This research aims to answer the following question (1) What materials are applied in listening lessons? (2) Are the students' listening skills good? (3)What effective methods do lecturers use for students? (4)Why do lecturers apply this method in their classes?(5) Is this an effective way to develop students' skills better?. Based on the information it can be concluded that listening plays a crucial role in language acquisition and proficiency. The document emphasizes the importance of developing effective listening skills to enhance language abilities and compete in a globalized world. Various strategies and techniques, such as using songs or TOEFL tests, are recommended to make listening activities more engaging and effective for students. These strategies aim to improve students' listening comprehension, pronunciation, and overall language skills. Furthermore, the document highlights the significance of incorporating music listening as a strategy to enhance English language learning. Music can serve as an engaging tool to present grammatical structures, new vocabulary, and rhymes in an entertaining way, thereby facilitating language acquisition.